CD4+ T cells facilitate replication of primary HIV-1 strains in macrophages and formation of macrophage internal virus-containing compartments - Victoria, Sabina (2025)
HIV-1 replication in macrophages is highly variable with internal virus accumulation in so-called virus-containing compartments (VCCs). VCCs represent a reservoir that is shielded from the antiviral immune response. VCC formation has been studied in lab-adapted HIV-1, but it has not been investigated whether primary HIV-1 strains induce VCCs. Furthermore, although macrophages transmit HIV-1 from VCCs to CD4+ T cells, the effect of T cells on VCCs is unknown. We analyzed the ability of primary and lab-adapted HIV-1 to replicate in macrophages, the effect of non-infected CD4+ T cell coculture, and VCC formation. All HIV-1 strains replicated in CD4+ T cells, whereas only lab-adapted HIV-1 replicated efficiently in macrophage monocultures. Coculture with non-infected CD4+ T cells enhanced the replication of primary HIV-1 in macrophages, a process associated with increased VCC formation and dependent on direct cell-to-cell contact. Broadly neutralizing antibodies differentially affectedaffectedaffectedCD4+ T cell-mediated enhancement of HIV-1 replication in macrophages. CD4 antibody treatment of macrophages phenocopied the infection-promoting effect of CD4+ T cell coculture. In conclusion, non-infected CD4+ T cells facilitate primary HIV-1 replication in macrophages, and the induction of VCCs appears to be a proxy for this phenotype. VCC formation and HIV-1 replication in macrophages are promoted by non-infected CD4+ T cells in a CD4- and GP120-dependent manner. Our findings highlight the critical role of T cell-macrophage interaction in HIV-1 replication dynamics and VCC formation and call for strategies to interfere with VCCs in order to target the HIV-1 reservoir in macrophages.